ADAPTING INTERNET PARENTAL MEDIATION SURVEY: A PILOT STUDY: Adaptasi Survei Mediasi Orang Tua dalam Penggunaan Internet: Studi Awal - Aliya Ulfa; Lenny Kendhawati; Marisa Fransiska Moeliono (Faculty of Social Science and Human Ecology, IPB University, 2025)
Adaptation of the parental mediation tool see how parents mediate children's internet for two main reasons, that culture can affect parenting and there is no measuring tool that looks at parenting that specifically looks at parental interactions with children's internet use. This study aims to report the results of the adaptation of parental mediation tool from Global Kids Online (GKO). In order to adapt this measurement tool to Indonesian, a pilot study was carried out. The participants of this study were 112 parents of early adolescents. In carrying out the adaptation, International Test Commision (ITC) Guidelines of Translating and Adapting Tests are used where there is a process of translation, review, and testing of instruments. Translation process was carried out using the back-translation method by a professional translator, the review was carried out by five people and the measuring instrument trials were processed with CTT and CFA for five parental mediation strategies. CTT results with item discrimination, factor loading, and reliability tests using Cronbach's alpha showed that with total of 42 items, two items were discarded. From CFA processing based on chi-square values, RMSEA, SRMR, CFI, and TLI, the adaptation of the measurement tools in this pilot study is fit and can be continued.